Establishment of a colony of Anopheles darlingi from French Guiana for vector competence studies on malaria transmission - Puchot, Nicolas; Lecoq, Marie-Thérèse; Carinci, Romuald; Duchemin, Jean Bernard; Gendrin, Mathilde; Bourgouin, Catherine (Frontiers in Tropical Diseases, 2022)
Anopheles darlingi is a major vector of both Plasmodium falciparum and Plasmodium vivax in South and Central America including French Guiana. However, the vector competence and physiology of this mosquito species have been scarcely studied due to difficulties in rearing it in the laboratory. Here, we report the successful establishment of a robust colony, from a mosquito collection in French Guiana. We describe our mosquito colonization procedure with relevant information on environmental conditions, mating ability, larval development, and survival, recorded over the first six critical generations. Experimental infection showed that our An. darlingi colony has a moderate permissiveness to in vitro produced gametocytes of the P. falciparum NF54 strain originating from Africa. This colony, which has reached its 21st generation, will allow further characterization of An. darlingi life-history traits and of Plasmodium–mosquito interactions with South American malaria parasites.